LINKING NEWS IN THE DIGITAL AGE: GRAMMATICAL COHESION AND INTERTEXTUALITY IN CNN INSTAGRAM NEWS CAPTION - Siti Rahmah Purba; Anni Holila Pulungan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines the use of grammatical cohesion and its contribution to the construction of intertextual meaning in Instagram news captions. Adopting a qualitative discourse analysis design, this research employs a descriptive qualitative method to analyze twenty-five captions selected purposively from CNN’s official Instagram account. The analysis is guided by Halliday and Hasan’s framework of grammatical cohesion—reference, substitution, ellipsis, and conjunction—and supported by the concept of intertextuality. The findings indicate that referential cohesion and conjunction are the most dominant cohesive devices, as they effectively maintain clarity and continuity in highly condensed texts. In contrast, substitution and ellipsis occur less frequently, reflecting a preference for explicit and unambiguous expression in digital news discourse. Despite their brevity, the captions demonstrate systematic linguistic organization that enables the efficient communication of complex information. Furthermore, the study reveals that intertextuality plays a significant role in meaning construction. The captions frequently draw on prior events, institutional discourse, and widely circulated public issues, allowing them to connect with broader news narratives without extensive elaboration. However, this reliance on shared knowledge positions readers as active participants in the interpretive process. Overall, the study demonstrates that grammatical cohesion and intertextuality function as complementary mechanisms in digital journalism, contributing to both textual coherence and contextual depth.